HEDGING IN ACADEMIC WRITING: PRAGMATIC FUNCTIONS AND LINGUISTIC STRATEGIES - Nurmaxmatova Firuza Rasulovna, (TADQIQOTLAR, 2026)
Abstract: Hedging is a key aspect of academic writing that helps authors show caution, probability, and openness to different interpretations. Instead of presenting claims as definite truths, scholars often soften their statements to convey uncertainty and adhere to discipline norms. This article looks at the language forms and practical uses of hedging in academic discussions. It draws on Ken Hyland's work and research from other discourse analysts. The study examines modal verbs, epistemic adverbs, reporting verbs, and other methods used to present cautious claims. The paper argues that  hedging  improves  credibility,  politeness,  and  objectivity  while  encouraging scholarly dialogue. The findings indicate that using hedging effectively is crucial for successfully engaging in academic communities.